Effects of ethanolic extract of Azadirachta indica leaves on lipid peroxidation and serum lipids of diabetic Wistar rats - Ekaidem, Itemobong S. (Acta Biologica Szegediensis, 2007)
The effects of ethanolic extract of Azadirachta indica leaves on lipid peroxidation and serum lipids ofalloxan-induced diabetic rats were examined to assess the role of the extract in the management diabetic complications. Serum Malondialdehyde (MDA), totál cholesterol, triglyceride and blood glucose were measured in diabetic and normál rats with or without 400 mg/kg leaf extract of A. indica. The result showed that blood glucose, totál cholesterol (TC), triglyceride and MDA concentrations in serum of untreated diabetic rats were significantly (P<0.05) higher than that of normál control and diabetic rats treated with the extracts. The extract caused a 55.8%, 27.1%, 16.8% and 64.7% reduction in blood glucose, TC, TG and MDA respectively when compared to untreated diabetic rats. The extract alsó demonstrated growth promoting effect on normál and diabetic rats. The anti-lipid peroxidative, antihyperglycaemic and serum lipid modulating activities justify the possible use of extract of A. indica leaves in the management of diabetic complications.